Knowledge of Mother Regarding Children Vaccines (Medico Legal Update, 2020)
Vaccines are important factors in the health system , and more benefit for the health and develops population,the study was conducted among chidden with age between one month to three yeas old age for period 4months from April to July 2018 , were data collection among mothers (N=300) attending primary healthcare center in Al-Noor City – Baghdad , were 120(48%) at age (26-30) years old ,125 (41.6%) with primaryeducation .